(untitled) (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
The article provides a comprehensive analysis of international and national approaches to identifying, preparing for, mitigating, and responding to emergencies. The effectiveness of risk management systems is studied based on strategies developed by international organizations, as well as the national experience of the Republic of Uzbekistan. Ways to reduce the negative consequences of emergencies through community participation, coordination, planning, and medical care mechanisms are considered. During the study, existing systems were analyzed using theoretical and practical methods, and recommendations for improvement were given.